Short Circuit: A Failing Technology for Administering Justice in Nunavut - Matyas, David (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2018)
If all you have is a hammer everything looks like a nail, but if all you have is a circuit court what happens to the administration of justice? This paper explores the history and contemporary usages of the itinerant ‘circuit court’ in the Canadian Arctic. Presenting the circuit court as a technology of justice, the paper explores why and how this instrument has been employed and the possibilities it constrains. Looking to the challenges of administering justice in contemporary Nunavut, the paper argues that a different type of technology may be needed: One that facilitates work, rather than exercises control; allows for specialized outcomes in place of compliant results; and that focusses on the growth of justice instead of products that are just. The paper concludes by exploring the local, sedentary, judge-based system of Greenland—steeped in its civilian procedural law—as a compelling alternative technology to the circuit court in Nunavut.